Let's evaluate each term in your expression step by step.
-
\( 3 \times (8^0) \):
- \( 8^0 = 1 \)
- So, \( 3 \times 1 = 3 \)
-
\( 5^0 + 9^0 \):
- \( 5^0 = 1 \) and \( 9^0 = 1 \)
- So, \( 1 + 1 = 2 \)
-
\( 13 - (7.42^0) \):
- \( 7.42^0 = 1 \)
- So, \( 13 - 1 = 12 \)
-
\( (-2.97^0) \):
- \( (-2.97)^0 = 1 \)
Now, let's summarize the results:
- The first term is \( 3 \).
- The second term is \( 2 \).
- The third term is \( 12 \).
- The fourth term is \( 1 \).
To find the overall answer to \( 3 \) (from the first term), \( 2 \) (from the second term), \( 12 \) (from the third term), and \( 1 \) (from the fourth term), we look for the possibility of combining these to reach one:
- The answer does not equal \( 1 \) based on the evaluations above. Each evaluated expression leads to higher values than \( 1 \).
None of the evaluated expressions equal \( 1 \), and the operation to combine them wasn't explicitly defined in your question. If you want a specific operation to combine these values, let me know, and I can assist further!